(untitled) (University Journal of Zoology, Rajshahi University, 2009)
Zooplankton populations of Sona Dighi were remarkable. In all 31 genera and 45 species represented by five major groups have been reported from Sona Dighi, Rajshahi based on a year investigation. The recorded groups were as follows as Protozoa (5 genera, 4 species), Rotifera (7 genera, 11 species), Cladocera (6 genera, 8 species), Ostracoda (4 genera, 6 species) and Copepoda (9 genera, 15 species).Physical chemical characteristics and zooplankton diversity of the reservoir indicates its eutrophic nature. Key words: Zooplankton, Sona Dighi, Rajshahi, Bangladesh. Â doi:10.3329/ujzru.v27i0.1945 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 07-11